REPRESENTASI GENDER PEREMPUAN DALAM PENGAMBILAN KEPUTUSAN PADA KELUARGA DI KABUPATEN SIMALUNGUN - Nabila Nur Atikah; Solihah Titin Sumanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Decision making is a definite step taken in looking for something solutions to problems that occur. In the family the decisions are usually taken over by men. However, at this time the decision was not only for men, but also for women also participate in decision making in the family. Research has a purpose to analyze gender representation in family decision making. This research uses a case study in Simalungun Regency, North Sumatra. Method the research used is a qualitative method. Collection of data sources is done using interview techniques directly to 10 respondents. Research result raises new conclusions where the female gender does not have a deep gap take decisions or policies in the family that are carried out jointly between husband and wife on domestic roles and public roles in society. In this case women share in the problems that exist in the family. With each other support and cooperation between husband and wife. So there is no difference between female and male.